Doxapram Use for Apnoea of Prematurity in Neonatal Intensive Care - S. A. Prins; S. J. A. Pans; M. M. van Weissenbruch; F. J. Walther; S. H. P. Simons (Hindawi Limited, 2013)
Apnoea of prematurity is treated with noninvasive respiratory therapy and methylxanthines. For therapy unresponsive apnoea doxapram is often prescibed in preterm neonates. The duration, dosage and route of administration of doxapram together with its efficacy was evaluated in two Dutch neonatal intensive care. Outcome concerning short-term safety and neonatal morbidity were evaluated. During 5 years, 122 of 1,501 admitted newborns <32 weeks of gestational age received doxapram. 64.8% of patients did not need intubation after doxapram. 25% of treated neonates were <27 weeks of gestation. A positive response to doxapram therapy on apnoea was associated with longer duration of doxapram usage (P<0.001), lower mean doses (P<0.003), and less days of intensive care (median 33 versus 42 days; P<0.002). No patients died during doxapram therapy. Incidence of necrotizing enterocolitis, intraventricular hemorrhage, periventricular leukomalacia, retinopathy of prematurity, persistent ductus arteriosus, or worsening of pulmonary condition did not increase during doxapram therapy. Doxapram is frequently used for apnoea of prematurity, despite a lack of data on short-term efficacy and long-term safety. Until efficacy and safety are confirmed in prospective trials, doxapram should be used with caution.